PEDAGOGIC FUNCTIONS OF TEACHERSâ€™ CODE-SWITCHING IN GARUDA BILINGUAL KINDERGARTEN - Pinatih, I Gusti Ayu Arya Satyani (Universitas Pendidikan Ganesha, 2019)
EvenÂ thoughÂ codeswitchingÂ hasÂ becomeÂ aÂ naturalÂ phenomenonÂ andÂ occurredÂ inÂ regularÂ basisÂ duringÂ the teachingÂ andÂ learningÂ processÂ inÂ bilingualÂ classroom,Â theÂ pedagogicÂ analysisÂ ofÂ theÂ occurringÂ switches shouldÂ beÂ takenÂ intoÂ accountÂ toÂ figureÂ outÂ whetherÂ theÂ switchesÂ areÂ indeedÂ aÂ pedagogicÂ toolÂ usedÂ by bilingualÂ teachersÂ forÂ theÂ comprehensionÂ andÂ achievementÂ ofÂ theÂ lessonÂ content.Â Therefore,Â the objectiveÂ ofÂ thisÂ studyÂ isÂ toÂ figureÂ outÂ theÂ functionsÂ ofÂ teachersâ€™Â codeâ€switchingÂ duringÂ classroom teachingÂ andÂ learningÂ processÂ inÂ GarudaÂ BilingualÂ Kindergarten.Â ThisÂ studyÂ wasÂ conductedÂ usingÂ a descriptiveÂ qualitativeÂ design.Â TheÂ dataÂ wereÂ collectedÂ throughÂ classroomÂ observationÂ andÂ recordings. TheÂ obtainedÂ dataÂ wereÂ analyzedÂ basedÂ onÂ theÂ codingÂ categoriesÂ ofÂ pedagogicÂ functionÂ theory.Â The findingsÂ indicateÂ thatÂ theÂ functionsÂ ofÂ theÂ occurringÂ codeâ€switchingÂ are:Â 1)Â instructionalÂ forÂ content acquisition,Â 2)Â reformulationÂ of content,Â 3)Â facilitation,Â andÂ 4)Â habitual.Â TheÂ resultÂ ofÂ thisÂ studyÂ is expectedÂ toÂ beÂ usefulÂ especiallyÂ forÂ teachersÂ toÂ knowÂ theÂ roleÂ ofÂ codeâ€switchingÂ inÂ supportingÂ the emergentÂ bilingualsÂ duringÂ classroomÂ teachingÂ and learningÂ processÂ asÂ wellÂ asÂ toÂ helpÂ teachersÂ planÂ a moreÂ effectiveÂ languageÂ strategy.